Japanese Universities' Fraught Relationship with the Modern Chinese Language. Issue 3 (1st September 2020) - Sinclair, Paul
ABSTRACT: This study argues that the massive growing interest in Chinese language in Japanese universities in the 1990s was more complicated than it seemed. 'Chinese fever' at the beginning of the new millennium is best situated in the context of several 'boom-and-bust' cycles in Chinese language education that date back to the early Meiji Period when the Japanese university system was beginning to take shape. This focusses on three key transitions: 1) the early 1870s, when Monbushō assumed control of foreign language education from the Gaimushō (Ministry of Foreign Affairs); 2) the mid-1940s, when the Allied General Headquarters (GHQ) made policy decisions that compromised the Chinese studies that had slowly taken root in the pre-war system; and 3) the late 1990s when Monbushō advanced internationalization policies that compromised Chinese language initiatives while interest in the language was burgeoning. In each case, 'homegrown' Chinese studies were poised to make some kind of dramatic comeback; in each case the best efforts of Chinese language's colorful protagonists were thwarted by politically-tinged government policy. This article contends that the western-oriented Japanese academy failed to nurture Chinese language education precisely at times when the environment for its growth was most fertile.